Proportions of Group B Streptococcus Isolation from Pregnant Women's Vaginal and Rectal Swab Specimens at a Tertiary Hospital in Surabaya, Indonesia - , Ivanna; Wasito, Eddy Bagus; Debora, Kartuti (Folia Medica Indonesiana, 2023)
Highlights: • Rectal and vaginal swab specimens were collected from pregnant women, and there was no significant difference in the proportions of group B Streptococcus isolation. • Combined vaginal and rectal swab cultures provide a higher isolation of group B Streptococcus. Abstract : Group B Streptococcus is a Gram-positive bacterium found in women. It causes high-risk mortality in pregnant women, newborns, and the elderly. This study aimed to compare group B Streptococcus (GBS/Streptococcus agalactiae) proportions from different collection sites (vaginal and rectal swabs). This was an analytic observational study with a hospital-based cross-sectional design. A total of 74 swabs were taken from 37 pregnant women at 35–37 weeks of gestation. Each participant provided a vaginal swab and a rectal swab, which were cultured in Todd Hewitt broth, blood agar, and CHROMagar. The specimens were subsequently identified using the VITEK 2 system. The GBS isolation percentages from the vaginal and rectal swab specimens were determined to be 13.5% and 8.1%, respectively. The McNemar test had a result of 0.697, and the Cohen's kappa test had a result of 0.165. To conclude, there was no significant difference in GBS isolation proportions between the vaginal and rectal swab cultures. Combined vaginal and rectal swab cultures were required to increase GBS isolation from pregnant women.